Analytical studies of the behaviour of semi-rigid non-sway frames with tubular columns - Ahmad Baharuddin Abd. Rahman 171778 (Sheffield, U.K. : University of Sheffield, 1999)
Thesis (Doctor of Philosophy) - University of Sheffield, 1999